2019
DOI: 10.1177/0267659119846789
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for euthyroid sick syndrome and its impact on in-hospital clinical outcomes in high-risk patients undergoing coronary artery bypass grafting

Abstract: Objective: The purpose of this cohort study was to investigate the independent relationship between euthyroid sick syndrome and in-hospital outcomes in high-risk patients undergoing isolated coronary artery bypass grafting, and we also examined the direct correlation between pre- or intra-operative variables and the incidence of coronary artery bypass grafting–associated euthyroid sick syndrome. Methods: The present study enrolled high-risk patients undergoing coronary artery bypass grafting from 1 January 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Studies were conducted between 2001 and 2020. There was a high risk of bias ( Table 1 ) resulting from the observational ( 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ) and retrospective study design ( 17 , 18 , 22 , 30 , 31 , 37 ) used in the studies. The absence of statistical control for known confounders ( 17 , 23 , 25 , 26 , 34 , 37 ) and for covariance with severity scores ( 24 , 35 ) was also identified.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies were conducted between 2001 and 2020. There was a high risk of bias ( Table 1 ) resulting from the observational ( 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ) and retrospective study design ( 17 , 18 , 22 , 30 , 31 , 37 ) used in the studies. The absence of statistical control for known confounders ( 17 , 23 , 25 , 26 , 34 , 37 ) and for covariance with severity scores ( 24 , 35 ) was also identified.…”
Section: Resultsmentioning
confidence: 99%
“…In Table 3 , we present the characteristics of the 25 included studies and the data on the association between serum TH levels and the outcome of critically ill patients. As to types of diseases, 14 studies presented information from patients admitted to ICU with non-specified clinical and surgical critical illness, 4 studies included patients admitted for cardiovascular causes – 2 from patients undergoing CABG ( 19 , 39 ) and 2 from decompensated heart failure ( 17 , 20 ), 3 studies included patients with sepsis ( 24 , 29 , 37 ), 1 study was on patients with polytrauma ( 21 ) and 1 study was from a burning trauma center ( 22 ). Mortality rates varied greatly since they derived from a heterogeneous population with different follow-up periods.…”
Section: Resultsmentioning
confidence: 99%
“…Other study monitored the dynamic levels of FT3 and found that decreased tendency in FT3 values was prominent on the postoperative second day, which is the most common day for arrhythmia following cardiac surgery ( 20 ). Interestingly, CABG-related euthyroid sick syndrome exerted detrimental effects on in-hospital adverse cardiovascular outcomes ( 21 ). Recently, off-pump CABG and one-stop hybrid coronary revascularization become the common effective ways of surgical coronary revascularization, which avoid the negative effects of cardiopulmonary bypass.…”
Section: Discussionmentioning
confidence: 99%
“…erefore, it is essential to develop prognostic models for accurately identify mortality and morbidity after isolated CABG, especially high-risk CABG. Research data proved that the Sequential Organ Failure Assessment (SOFA) score per se as an independent risk factor for mortality after CABG and SOFA could be regarded as the most effective prognostic model for guiding the use of preventive and early therapeutic strategies to reduce mortality and morbidity for patients undergoing high-risk CABG [2,3]. Recently, SOFA maximum is recommended to assess multiorgan dysfunction over time and severe multiorgan failure, measured by SOFA maximum greater than 11, predicted an in-hospital mortality of 95% [3,4].…”
Section: Introductionmentioning
confidence: 99%